Pollinator species richness and abundance across diverse habitat-types on Terceira Island (Azores, Portugal) - Mário Boieiro; Raúl Oliveira; Ricardo Costa; Paulo Borges (Biodiversity Data Journal)
Azorean biodiversity is relatively well-known following important scientific contributions during the last three decades. These have set a comprehensive species checklist for the Archipelago, improved significantly the knowledge on species abundance, ecology and distribution and have contributed to define priorities for conservation management and scientific research. Nevertheless, despite these efforts, a key functional group - the pollinators - remains poorly known in Azores, including their occurrence in different habitat-types and islands. Insect pollinators play a key ecological role and a valuable ecosystem service being crucial to having basic information on their abundance, distribution and ecology and a good knowledge on the status of their populations, if we aim to ensure the long-term sustainability of terrestrial ecosystems. Furthermore, island ecosystems are facing significant pressures from land-use and climatic changes and, from the increasing arrival of alien species to these remote areas, presenting a pressing need to assess the effects of these factors on island pollinators and pollination.Here, we present an inventory of the pollinator species found in different habitat-types of Terceira along a gradient of disturbance and encompassing 30 sites distributed throughout the island. We identified 2547 pollinators from 40 taxa, mostly dipterans and hymenopterans and recorded novel information on species distribution and ecological associations. A high number of taxa are native species, including three Azorean endemics, but 14 species are alien to the Archipelago. The use of a combination of standardised sampling techniques allowed us to collect information on diverse pollinator groups, but, most importantly, the data collected will contribute to assess the impacts of human activities on pollinator abundance and richness and support decision-making on habitat management for pollinators in the Azores.